The Major Influence of Thomas Nast’s Political Cartoons on 19th Century American Politics - Szélpál, Lívia (AMERICANA E-journal of American Studies in Hungary, 2023)
The aims of this paper are first to present Thomas Nast’s oeuvre; second, to scrutinize the role of humor and the power of Nast’s cartoons in mid-19th century American politics and presidential elections; and finally, to illustrate his role as a proto-muckraker using the medium of cartoons to expose the corruption of the political machine. I would argue that his political cartoons fulfilled society’s essential criticizing and controlling function and encouraged opinion formation and decision-making as well by providing humorous and entertaining perspectives in the newspapers. As a part of my research, I have selected three of his political cartoons, representing the many-sided character of Nast’s oeuvre at the zenith of his carrier before the President Hayes Compromise of 1877, which are the following: (1) Nast as a proto-muckraker journalist, (2) Nast as a fallible human who attacked Victoria Woodhull by drawing a cartoon as a critical answer for her support of free love, and finally (3) the role of animal symbols in his political cartoons and his “invention” of the political party animals.